Genome-wide identification of the HD-ZIP IV gene family in Pogostemon cablin and its association with glandular hair development - Xie, Shuqi; Li, Yiling; Liao, Huiting; Chen, Wenyi; Zhang, Yuqi; Yan, Xiaoming; Zhang, Hongyi; He, Mengling; Yan, Hanjing (Frontiers in Plant Science, 2025)
BackgroundHD-ZIP IV transcription factors are a plant-specific subgroup of the homeodomain-leucine zipper (HD-ZIP) family, known to regulate epidermal cell differentiation. While their functions have been studied in many plant species, their roles in Pogostemon cablin (patchouli) remain largely unexplored.MethodsWe conducted a comprehensive genome-wide identification and analysis of HD-ZIP IV genes in patchouli. Phylogenetic relationships, gene structures, conserved motifs, and promoter cis-elements were examined. Expression patterns under hormone treatments were analyzed using qRT-PCR. Correlation analyses and virus-induced gene silencing (VIGS) were employed to assess gene function in glandular trichome development.ResultsA total of 38 HD-ZIP IV genes (PcHDZIV1–PcHDZIV38) were identified and classified into six subfamilies. Gene structure and motif analyses revealed conserved features within subgroups. Promoter analysis indicated widespread involvement in light, hormone, and stress responses. Many PcHDZIV genes showed dynamic responses to exogenous hormone treatments (MeJA, IAA, SA). Notably, PcHDZIV5 expression correlated strongly with glandular trichome density, and VIGS experiments confirmed its role in promoting trichome development.DiscussionOur findings suggest that hormone signaling may regulate PcHDZIV5 expression, indirectly influencing glandular trichome formation in patchouli. This study lays a foundation for further functional characterization of HD-ZIP IV genes in patchouli and advances understanding of the molecular mechanisms underlying trichome development.